Cannabis Use Is Associated With Increased Levels of Soluble gp130 in Schizophrenia but Not in Bipolar Disorder - Szabo, Attila; Akkouh, Ibrahim A.; Ueland, Thor; Lagerberg, Trine Vik; Dieset, Ingrid; Bjella, Thomas; Aukrust, Pål; Le Hellard, Stephanie; Stavrum, Anne-Kristin; Melle, Ingrid; Andreassen, Ole A.; Djurovic, Srdjan (Frontiers in Psychiatry, 2020)
The complex effects of plant cannabinoids on human physiology is not yet fully understood, but include a wide spectrum of effects on immune modulation. The immune system and its inflammatory effector pathways are recently emerging as possible causative factors in psychotic disorders. The present study aimed to investigate whether self-administered cannabis use was associated with changes in circulating immune and neuroendocrine markers in schizophrenia (SCZ) and bipolar disorder (BD) patients. A screening of 13 plasma markers reflecting different inflammatory pathways was performed in SCZ (n=401) and BD patients (n=242) after subdividing each group into cannabis user and non-user subgroups. We found that i) soluble gp130 (sgp130) concentrations were significantly elevated among cannabis users in the SCZ group (p=0.002) after multiple testing correction, but not in BD. ii) Nominally significant differences were observed in the levels of IL-1RA (p=0.0059), YKL40 (p=0.0069), CatS (p=0.013), sTNFR1 (p=0.031), and BDNF (p=0.020), where these factors exhibited higher plasma levels in cannabis user SCZ patients than in non-users. iii) These differences in systemic levels were not reflected by altered mRNA expression of genes encoding sgp130, IL-1RA, YKL40, CatS, sTNFR1, and BDNF in whole blood. Our results show that cannabis self-administration is associated with markedly higher sgp130 levels in SCZ, but not in BD, and that this phenomenon is independent of the modulation of peripheral immune cells. These findings warrant further investigation into the potential IL-6 trans-signaling modulatory, anti-inflammatory, neuroimmune, and biobehavioral-cognitive effects of cannabis use in SCZ.